À la recherche de la liberté humaine. Débat contemporainchrétien sur la liberté - Skobel , Stanisław (Warszawskie Studia Teologiczne, 2019)
Reflection on human freedom will remain a constant motive for reflection in moral theology. Without freedom, there is no human act, so there is no morality in the strict sense of the term “freedom”. That is why it is worth returning to the issue of freedom, but taking into account new ways of understanding it. Freedom will remain a current problem in the struggle of man for good, especially in social life. For Christian thought on this subject, the encyclical of John Paul II Veritatis splendor will remain relevant – read it again.